Education for Sale - Midwinter, Eric (Routledge Library Editions: Education, 1977)
Teachers, schools and education authorities invariably hide their considerable lights and their public relations techniques are often inadequate for broadcasting the invaluable work accomplished in schools. This book offers clear-cut and highly–practical advice for every teacher from pre-school to sixth form on how to get the educational message across to parents. Over the past decades it has become an acute professional concern for teachers to involve parents as closely as possible in the educational process. The book acknowledges that educational salesmanship must be adapted to the cultural norms of its customers and that many teachers, because of their background and training, have reservations about their role as publicists. Set out here is a logical and orderly path of action to help everyone from the most extrovert to the most diffident.